Staropolska Ars legendi Biblii. Historia o Heliaszu proroku (1572) – metoda pracy poety nad parafrazą: Old Polish Ars legendi of the Bible. Historia o Heliaszu proroku (1572) – the poet’s method of working on paraphrase - Krzysztofik, Małgorzata (Prace Polonistyczne, 2019)
The article is devoted to characteristics of the method of paraphrasing biblical text found in the anonymous Historia o Heliaszu proroku from the Third Book of Kings (1572). I discuss the composition of the text, its elements of cultural adaptation and to what extent the religious romance is faithful to the canonical pattern. The comparison of paraphrases with the relevant passages of the Bible makes it clear that the poet was focused on an interesting story with fast-changing action. Therefore, he shortened or skipped those Bible episodes loosely related to the history of Elijah, as well as descriptive and information-reporting fragments. He made cultural adaptations, but he was inconsistent in these. The author worked hard to maintain a similarity with The Scriptures. He expanded the meaning of the Bible verse by inserting various functions (prosodic, commenting, explaining, characterizing, evaluating), without fundamentally changing the meaning of the original text. He did not allude to his contemporary times, events nor characters. He did not interpret the Old Testament in a New Testament context. He did not add prayers and did not supplement the text with marginal remarks. The poetic beauty of the paraphrases was of secondary value; the didactic and moralizing tone of the work was the most important for the author.